Pengaruh Air Gambut Terhadap Karakteristik Marshall Pada Campuran AC-WC Yang Menggunakan Abu Tandan Sawit Sebagai Filler - Putra, Muhammad Rifal Fan; Malik, Alfian; Alwinda, Yosi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Asphalt mixture for highway pavement consists of aggregate, filler, and asphalt. Materials commonly used as fillers are cement, sand, lime, and rock ash. These materials have limited availability, are relatively expensive, and are nonrenewable materials. One of the alternatives to the filler is oil palm bunch ash which is a waste of the palm oil processing industry and is a renewable natural resource. The purpose of this study was to determine the effect of peat water on the characteristic value of the Marshall AC-WC mixture with oil palm bunch ash as filler. This study used the asphalt content used in the determination of KAO of 5.5%, 6%, 6.5%, 7%, and 7.5%. While the variations filler used were 0%, 2%, 4%, 6%, and 8%. This research was conducted under the General Specifications of Bina Marga 2018. The results of this study show that the AC-WC layer mixture when immersed in peat water has an increased KAO value in the range of 6.08% 7.30%, for variations of filler 6% and 8%. not obtained because the characteristic parameters Marshall do not meet the specifications and the value of stability and durability has decreased. The filler 4%with immersion time of 0.5 hours gave the highest stability value of 919.93 kg, while the lowest yield was obtained at filler 0% with 24 hours soaking time of 513.80 kg. For Variations of filler 0%, 2%, and 4% with soaking time of up to 3 hours, the IKS value is more than 90% so that it meets the specifications. Keywords: Palm Bunch Ash, Filler, Peat Water, AC-WC